THE EFFECT OF WORK MOTIVATION, WORK DISCIPLINE, AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE AT AGHARA COFFEE ROASTER - Novita Br. Simanjuntak; Ewi Br. Sihombing; Galli Kurnia Dinda; Lenta Friska Purba; Yan Raja David Hamonangan Damanik (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to determine and analyze the influence of work motivation, work discipline and job satisfaction on employee performance at Aghara Coffee Roaster. This type of research uses quantitative research. The research sample was 30 respondents. The data analysis method used multiple linear regression analysis. Based on the results of the t hypothesis test, it can be concluded that work motivation has a significant effect on employee performance with a calculated tvalue of 3.797> ttable 2.055 and a significance value of 0.000 < 0.05, work discipline has a significant effect on employee performance with a calculated tvalue of 2.303 > ttable 2.055 and a significance value of 0.030 < 0.05 and job satisfaction has a significant effect on employee performance with a calculated tvalue of 3.341> ttable 2.055 and a significance value of 0.003 < 0.05. Based on the results of the F hypothesis test, it can be concluded that simultaneously/together work motivation, work discipline and job satisfaction have an effect on employee performance with an Fcount value of 28.508 > Ftable 2.975 and a significance value of 0.000 < 0.05. Based on the analysis of the coefficient of determination, the coefficient of determination or Adjusted R-Square value of 0.740 or 74% of work motivation, work discipline and job satisfaction has an effect on employee performance, while 26% is the influence of other variables that did not participate in this study.